Some More Results on at Most Twin Extendable Separated Domination Number of a Graphs - Anuthiya, S.; Mahadeven, G. (Journal of physics. Conference series, 2021)
Previously, G. Mahadevan et. al., has invented the concept of At most twin Extendable separate Domination number of a graph and obtained many resluts. A set S ⊆ V is said to be At most twin extendable separated dominating set, if for every vertex υ ∈ V − S, 1 ⩽ | N (V) ∩ S| ⩽ 2 and < V − S > is a perfect matching. The minimum cardinality taken over all At most twin extendable separated dominating sets is called At most twin extendable separated domination number of a graph and it is denoted by ATES (G). In this research paper, this number is evaluated for some intersting special types of graphs.